Bioavailability of vitamin D biofortified pork meat: results of an acute human crossover study in healthy adults. (17th February 2023) - Neill, H. R.; Gill, C. I. R.; McDonald, E. J.; McRoberts, W. C.; McAleenon, R.; Slevin, M. M.; Cobice, D.; McMurray, R.; Loy, R.; White, A.; Pourshahidi, L. K.
Abstract: Vitamin D intakes are concerningly low. Food-based strategies are urgently warranted to increase vitamin D intakes and subsequently improve 25-hydroxyvitamin D (25(OH)D) concentrations. This acute randomised three-way crossover study investigated the efficacy of vitamin D biofortified pork derived from pigs exposed to UVB light to increase serum 25(OH)D3 concentrations, compared to a dose-matched vitamin D3 supplement and control pork in adults ( n = 14). Blood samples were obtained at baseline and then 1.5, 3, 6, 9 and 24 h postprandially. There was a significant effect of time ( p < 0.01) and a significant treatment*time interaction ( p < 0.05). UV pork and supplement significantly increased within-group serum 25(OH)D3 concentrations over timepoints ( p < 0.05) (max. change 0.9 nmol/L (2.2%) UV pork, 1.5 nmol/L (3.5%) supplement, 0.7 nmol/L (1.9%) control). Vitamin D biofortified pork modestly increased 25(OH)D3 concentrations and produced a similar response pattern as a dose-matched vitamin D supplement, but biofortification protocols should be further optimised to ensure differentiation from standard pork.